Aggressive NK-Cell Leukemia - Ishida, Fumihiro (Frontiers in Pediatrics, 2018)
Aggressive NK cell leukemia (ANKL) is a rare malignant lymphoproliferative disorder of mature NK cells closely associated with Epstein-Barr virus (EBV) and more common in East Asia than in other areas. Significant variations exist in the morphology of ANKL tumor cells, from typical large granular lymphocyte morphology to highly atypical features with basophilic cytoplasm containing azurophilc granules. The main involved sites are hepatosplenic lesions, bone marrow and peripheral blood, and nasal or skin lesions are infrequent. A fever and liver dysfunction with an often rapidly progressive course are the main clinical symptoms, including hemophagocytic syndrome and disseminated intravascular coagulation. Although the outcome had been dismal for decades, with a median survival of less than three months, the introduction of combined chemotherapy including L-asparaginase and allogeneic hematopoietic cell transplantation has helped achieve a complete response and potential cure for some patients. With the advent of next-generation sequencing technologies, molecular alterations of ANKL have been elucidated, and dysfunctions in several signaling pathways, including the JAK/STAT pathway, have been identified. Novel target approaches to managing these abnormalities might help improve the prognosis of patients with ANKL.